2017
DOI: 10.1038/s41598-017-02314-x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolite genes encoded by potato rhizosphere microbiomes in the Andean highlands are diverse and vary with sampling site and vegetation stage

Abstract: Potato (Solanum tuberosum) is an important staple crop worldwide, it has been cultivated in the Andean Altiplano under low-input farming practices at high altitudes and under harsh environment for centuries. We analyzed secondary metabolite (SM) gene diversity encoded in the potato rhizosphere microbiome during plant growth at three distinct sites located in the Andes at high altitudes by 454-pyrosequencing of non-ribosomal peptide and polyketide biosynthetic genes. Phylogenetic analysis indicated that the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Taxonomic analysis showed that in both the rhizosphere and rhizoplane, the relative abundance of Actinobacteria was significantly lower in MI and Firmicutes was significantly lower in MU and MI when compared with NP ( Figure 3 ). This is in line with previous findings where members of Firmicutes and Actinobacteria were consistently associated with pathogen antagonism and soil disease suppression [ 31 , 32 , 33 ]. Xiong et al [ 28 ] compared microbial communities in suppressive- and conducive-soils associated with Fusarium wilt disease and found that Actinobacteria and Firmicutes were strongly enriched in the suppressive soil in a vanilla long-term continuous cropping system.…”
Section: Discussionsupporting
confidence: 93%
“…Taxonomic analysis showed that in both the rhizosphere and rhizoplane, the relative abundance of Actinobacteria was significantly lower in MI and Firmicutes was significantly lower in MU and MI when compared with NP ( Figure 3 ). This is in line with previous findings where members of Firmicutes and Actinobacteria were consistently associated with pathogen antagonism and soil disease suppression [ 31 , 32 , 33 ]. Xiong et al [ 28 ] compared microbial communities in suppressive- and conducive-soils associated with Fusarium wilt disease and found that Actinobacteria and Firmicutes were strongly enriched in the suppressive soil in a vanilla long-term continuous cropping system.…”
Section: Discussionsupporting
confidence: 93%
“…Especially, we found the seed-associated microbiome could be a reservoir and supplement of secondary metabolic capabilities, in addition to the host plant genome. Just as Aleti et al found, the secondary metabolite genes encoded by potato rhizosphere microbiomes were diverse and vary with the different samples and vegetation stage, which influence on the growth and metabolism of the host plant [ 70 ]. Our study suggested that some core taxa of seed microbiome not only promoted seed germination and plant growth, but also regulated and participated in the secondary metabolism of host plants.…”
Section: Discussionmentioning
confidence: 99%
“…This 'biosynthetic dark matter' can now be accessed by high throughput sequencing techniques and have high potential to provide a number of novel lead structures and compounds (Katz and Baltz, 2016). Due to adaptation to different host niches, differences in the chemical composition of plant hosts and the intense interaction with other microorganisms on and in plants, the plant microbiome provides a hotspot of specific and diverse metabolic and enzymatic potential of microorganisms (Aleti et al, 2017;Hassani et al, 2018). Indeed, sequence comparison within Firmicutes has revealed an enrichment of genomic clusters responsible for secondary metabolite production particularly in those strains, which have been found in association with plants (Aleti et al, 2015).…”
Section: Plant Microbiota As a Huge Reservoir Of Novel Bioactivitiesmentioning
confidence: 99%